A new sentiment index for the Islamic stock market. Issue 2 (3rd April 2019) - Asif Khan, Muhammad; Ahmad, Rubi; Azmi, Anna; Akbar, Muhammad
ABSTRACT: This study attempts to examine the predictability of Google search volume (GSV) and to construct an appropriate investor sentiment index for Islamic stock markets for seven United States (US) Islamic stock indices. Using principal component analysis, we construct an appropriate investor sentiment index for Islamic stock markets that depicts more persistent and higher R -squared values for all these seven US Islamic stocks indices compared to the original Financial and Economic Attitudes Revealed by Search (FEARS) sentiment index of Da, Engelberg, and Gao (2015). The observed results can be attributed to the construction of our investor sentiment index as we have included keywords active in the Islamic stock markets. The findings of this study provide strong predictability evidence for our new sentiment index in the Islamic stock markets.